Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E Torres; González, G Montero; Suárez, M A; Cámara, D E L A; Torres Álvarez, E; Montero González, G; Suárez de la Cámara, M A (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
Keywords: cork-oak; Quercus suber; silviculture; stand density

INFLUENCIA DE LA DENSIDAD DE LA MASA EN LA CALIDAD Y PRODUCCION DE CORCHO EN LOS ALCORNOCALES DE CORTES DE LA FRONTERA (MALAGA) - Montero, G; TORRES, E; Suárez, M A; Ortega, C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The influence of stand density on cork yield was evaluated for the Cortes de la Frontera (Spain) cork oak stand. Fifty five experimental plots were installed. The modular values of several variables which define cork oak yield potential of a tree, are presented by stand densitY'clusters (basal area groups). Likewise, many stand variables for different basal areas were studied
Keywords: cork-oak; silviculture; stand density